The N- and C-Terminal Regions of Rotavirus NSP5 Are the Critical Determinants for the Formation of Viroplasm-Like Structures Independent of NSP2 - Mohan, K. V. K. (American Society for Microbiology, 2003)
Molecular events and the interdependence of the two rotavirus nonstructural proteins, NSP5 and NSP2, in producing viroplasm-like structures (VLS) were previously evaluated by using transient cellular coexpression of the genes for the two proteins, and VLS domains as well as the NSP2-binding region of NSP5 were mapped in the context of NSP2. Review of the previous studies led us to postulate that NSP2 binding of NSP5 may block the N terminus of NSP5 or render it inaccessible and that any similar N-terminal blockage may render NSP5 alone capable of producing VLS independent of NSP2. This possibility was addressed in this report by using two forms of NSP5-green fluorescent protein (GFP) chimeras wherein GFP is fused at either the N or the C terminus of NSP5 (GFP-NSP5 and NSP5-GFP) and evaluating their VLS-forming capability (by light and electron microscopy) and phosphorylation and multimerization potential independent of NSP2. Our results demonstrate that NSP5 alone can form VLS when the N terminus is blocked by fusion with a nonrotavirus protein (GFP-NSP5) but the C terminus is unmodified. Only GFP-NSP5 was able to undergo hyperphosphorylation and multimerization with the native form of NSP5, emphasizing the importance of an unmodified C terminus for these events. Deletion analysis of NSP5 mapped the essential signals for VLS formation to the C terminus and clearly suggested that hyperphosphorylation of NSP5 is not required for VLS formation. The present study emphasizes in general that when fusion proteins are used for functional studies, constructs that represent fusions at both the N and the C termini of the protein should be evaluated.